Implementasi Bermain Model “ASYIK” Untuk Meningkatkan Semangat Belajar Anak Melalui Kegiatan Outbound Di TK Aisyiyah Bustanul Athfal 46 Daun - Susy Humayrah; Sri Watini (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
Early childhood education should not only be academically oriented, but should be able to provide new learning experiences for children. Therefore, teachers are required to be more creative and innovative in creating learning methods that are considered to be able to increase the enthusiasm and enthusiasm of students, namely through outbound activities. In addition to increasing children's enthusiasm for learning, outbound can also develop children's self-confidence, talents, and potential. This study aims to increase children's enthusiasm for learning through "Fun Rewards". The "Reward Fun" method is a new learning innovation model developed by Watini who has obtained a copyright for her work from the Ministry of Law and Human Rights of the Republic of Indonesia. The method we use in this research is CAR (Classroom Action Research). In the "Fun" Play method, there is a learning design, especially for early childhood through systematically structured learning steps or procedures. Activities start from initial activities, core activities, and final activities in which there are elements of 3B (Singing, Playing, and Moving) and have distinctive songs, yells, and rewards.